Development of Children's Interest and Talent Test Using the Fuzzy Logic Method: Pengembangan Test Minat Dan Bakat Anak-Anak Menggunakan Metode Fuzzy Logic - Tri Monarita Johan; Febriyanno Suryana; Jeprimansyah Jeprimansyah; Raimon Efendi (Lembaga Pengembangan dan Inovasi Universitas Dharmas Indonesia, 2022)
Interest means a high tendency of the heart towards something, also interpreted as passion or desire. Interest in children will begin to appear at pre-school age (3-5 years) to school age (6-12 years). And talent is defined as intelligence, traits and traits that are brought from birth, talents possessed by a person are believed to come from genetic patterns or DNA sequences that they carry. The role of parents is very important to detect how the interests and talents of children from an early age, to determine the interests and talents of children can be with the help of experts, namely child psychologists. But at this time there is still reluctance from parents to discuss their child's matter with a psychologist, starting from economic factors with the high cost of consulting and the lack of a number of psychologists which is not proportional to the growth of Indonesia's population. The goal to be achieved in this research is that by building a test of children's interests and talents, it is hoped that it can help parents to find out how their children's interests and talents are from an early age to prepare a quality successor of the nation without the help of experts, in this case child psychologists, whose numbers are still very small. minimal and high consulting fees.